Ion Channels Orchestrate Pancreatic Ductal Adenocarcinoma Progression and Therapy - Hofschröer, Verena; Najder, Karolina; Rugi, Micol; Bouazzi, Rayhana; Cozzolino, Marco; Arcangeli, Annarosa; Panyi, Gyorgy; Schwab, Albrecht (Frontiers in Pharmacology, 2021)
Pancreatic ductal adenocarcinoma (PDAC) is a devastating disease with a dismal prognosis. Therapeutic interventions are largely ineffective. A better understanding of the pathophysiology is required. Ion channels contribute substantially to the "hallmarks of cancer". Their expression is dysregulated in cancer and they are "misused" to drive cancer progression, but the underlying mechanisms are unclear. Ion channels are located in the cell membrane at the interface between the intracellular and extracellular space. They sense and modify the tumor microenvironment that in itself is a driver of PDAC aggressiveness. Ion channels detect e.g. locally altered proton and electrolyte concentrations or mechanical stimuli and transduce signals triggered by these microenvironmental cues through association with intracellular signaling cascades. While these concepts have been firmly established for other cancers, evidence has emerged only recently that ion channels are drivers of PDAC aggressiveness. Particularly, they appear to contribute to two of the characteristic PDAC features: the massive fibrosis of the tumor stroma (desmoplasia) and the efficient immune evasion. Our critical review of the literature clearly shows that there is still a remarkable lack of knowledge with respect to the contribution of ion channels to these two typical PDAC properties. Yet, we can draw parallels from ion channel research in other fibrotic and inflammatory diseases. Evidence is accumulating that pancreatic stellate cells express the same "pro-fibrotic" ion channels. Similarly, it is at least in part known which major ion channels are expressed in those innate and adaptive immune cells that populate the PDAC microenvironment. We explore potential therapeutic avenues derived thereof. Since drugs targeting PDAC-relevant ion channels are already in clinical use we propose to repurpose those in PDAC. The quest for ion channel targets is both motivated and complicated by the fact that some of the relevant channels, e.g. KCa3.1, are functionally expressed in the cancer, stroma and immune cells. Only in vivo studies will reveal which arm of the balance we should put our weights on when developing channel-targeting PDAC therapies. The time is up to explore the efficacy of ion channel targeting in (transgenic) murine PDAC models before launching clinical trials with repurposed drugs.